Land cover change and ethnoecological practices in Forest Management Unit XXV, North Sumatra, Indonesia - SAMSURI SAMSURI; ANITA ZAITUNAH; ARY SAMSURA; HOREB Y. MARBUN (Society for Indonesian Biodiversity, 2025)
Abstract. Samsuri, Zaitunah A, Samsura A, Marbun HY. 2025. Land cover change and ethnoecological practices in Forest Management Unit XXV, North Sumatra, Indonesia. Biodiversitas 26: 4545-4556. Forest management unit (FMU) is important site-level managers included in the sustainability of productivity. This concept is closely related to land tenure conflicts, which are influenced by community livelihood, local knowledge, traditional customs, environmental capacity, and local institutions. The dynamics of change in local knowledge, traditional customs, and population growth can increase the need for land and negatively impact biodiversity. Therefore, this research aims to (i) analyze land cover change and indigenous local knowledge, and (ii) examine the correlation between land cover change with community ethnoecological practices in FMU, North Sumatra. Landsat 5 and 8 Operational Land Imager (OLI) images were used to identify land cover change. Furthermore, the contingency coefficient correlation method was used to examine the relationship between land cover change and ethnoecology. The results showed that 10 land cover categories were identified, including water bodies, forest, paddy field, rubber estate, shrubs, bare land, mangroves, rubber, oil palms, and mixed garden. Rubber plantations experienced the most significant land area loss between 2001 and 2020, decreasing by 1,918.8 hectares. Meanwhile, mixed gardens reported a substantial gain of 6,171.8 hectares. The interviews identified 6 ethnoecological elements of the community, namely indigenous knowledge, medicinal plants, wood use, wild animal hunting, non-timber forest products, and traditional events. There was no significant correlation between land cover and community ethnoecological change. Despite the absence of a direct statistical relationship, these persistent practices provide crucial indirect support for in-situ biodiversity conservation within the managed forest landscape. In this context, the conversion of agricultural land and the destruction of forest in FMU areas must be addressed. The community indirectly supports the concept through planting and maintaining local species in mixed gardens. The continued cultivation of native species in community-managed gardens contributes indirectly to biodiversity conservation in FMU area despite the lack of significant correlation.